Cyberspace, cybersecurity, and cybercrime - Kremling, Janine (SAGE, 2018)
Preface -- Cyberspace -- What is cybersecurity -- Threat factors -- Threats factors ? computers as a tool -- Threats to cybersecurity by hacktivists and nation states -- Nationstate threat analysis -- Cyberterrorism -- Evolving threat: the deep web -- Cybersecurity operations -- Cyber security policies and legal issues -- What the future holds